Improving p-to-n transition and detection range of bimodal hydrogen-sensitive nanohybrids of hole-doped rGO and chemochromic Pd-decorated-MoO3 nanoflakes - Duy, Le Thai; Lee, Gyuyeon; Kim, Jinseo; Ahn, Byungmin; Cho, In Sun; Yu, Hak Ki; Seo, Hyungtak (Journal of Alloys and Compounds, 2019)
Detection of hydrogen (H2) over a wide concentration range (from parts-per-million levels to 4%) is necessary for safety in using hydrogen-fuel cell systems. For this purpose, our development of H2 sensitive nanohybrids of reduced graphene oxide (rGO) and chemochromic palladium-decorated molybdenum trioxide (Pd:MoO3) nanoflakes is presented. Additionally, the nanohybrids were employed as the active channel in a thin film transistor platform to invest informative characteristics for understanding their electrical properties and sensing mechanism. Through sensing measurements, (i) phenomena relating to response saturation and reversed behavior of gas sensors towards high exposure doses (i.e., p-to-n transition) and (ii) doping effects on the p-to-n transition and detection range of the hybrid materials are clarified. With combining electrical and visual output signals, the bimodal devices using the hole-doped nanohybrids can detect H2 over a wide concentration range (from 10 ppm to over 10%) at room temperature. Our results reveal opportunities for further development and improvement of hybrid nanomaterials and chemical sensors having a large sensing capability.
Keywords: Bimodal; Chemochromic nanoflake; Concentration ranges; Detection range; Hybrid nanomaterials; Molybdenum trioxide; Reduced graphene oxides (RGO); Response saturation; Bimodal; Chemochromic nanoflake; Hydrogen; p-to-n transition; Reduced graphene oxide; Wide detection range